Can the green credit policy enhance firm export quality? Evidence from China based on the DID model - Yang, Ge (Frontiers in Environmental Science, 2022)
The green credit policy is a crucial tool that the Chinese government adopted to tackle environmental problems by combining environmental regulation and credit policy. This study takes the Green Credit Guidelines (GCG) issued in 2012 as a quasi-natural experiment to examine its impact on the export quality of firms. Using data covering Chinese A-share listed firms and the difference-in-difference (DID) method, the empirical research shows that the GCG significantly enhanced the export quality of heavily polluting firms. The mediation analyses indicate that green innovation plays an intermediate role in enhancing the export quality of firms. The heterogeneity analysis of firm characteristics demonstrates that the improvement effect brought by the GCG is significantly reflected in state-owned firms and firms in financially underdeveloped areas. The research results provide implications for firms on how to deal with the green credit policy. In addition, it also serves as an essential reference for developing economies on the successful implementation of market-based environmental regulations.